Investigating the Relationship Between Budgeting Practices and Health Wellness Among Senior Citizen Social Pensioners (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the association between budgeting practices and health wellness among senior citizen social pensioners in Mogpog, Marinduque, Philippines. Anchored on the Theory of Planned Behavior and Dunn’s Theory of Wellness, a quantitative descriptive–correlational design was employed involving 263 senior citizen social pensioners from 11 barangays. Data were collected using a validated survey instrument measuring budgeting practices attitude toward budgeting, subjective norms, perceived behavioral control, behavioral intention, and actual budgeting behavior and health wellness across physical, mental, and social dimensions. Descriptive statistics, reliability testing, non parametric tests, and multivariate analysis were used to ensure analytical rigor. Results revealed that respondents generally demonstrated strong budgeting practices (grand mean = 3.89) and favorable health wellness outcomes (grand mean = 4.18). However, correlation and multivariate analyses indicated no statistically significant association between budgeting practices and health wellness (rs = 0.05, p = 0.42). Significant differences in budgeting practices were observed when respondents were grouped by gender and living arrangement, while no significant differences were found across marital status and educational attainment. The findings suggest that among low-income senior citizens reliant on social pensions, wellness is shaped more by structural and social determinants such as healthcare access, family support, and pension adequacy than by individual financial behavior alone. The study underscores the need for integrated financial, health, and social support interventions to enhance elderly well-being in rural communities.